Information and Institutions: The Relationship Between the Executive and Legislature in Botswana - Serema, Batlang Comma (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
Researchers who study legislatures contend that groups rather than institutions shape policy. This argument forms from perceptions that institutions are unimportant because power has been transferred away from Parliament toward policy communities of actors. Accordingly, it is thought that the institutional framework bears no significance because formal institutions for scrutinising decisions do not have a great impact on policy outputs and outcomes. The thesis of this paper is that differences in access and quality of information accords the Executive an advantage on policy formulation and analysis, a factor that is meagrely extended to constituency representatives. The paper examines information availability and its significance among parliamentary stakeholders, particularly MPs. It is through this analysis that a critique of the status quo will be provided. The paper is directed by the assumption that access to quality information equips the decision maker with informed alternatives pertaining to a particular subject. Constituency representatives in Botswana lacks an elaborate information system. By contrast the Ministers have an army of information providers (bureaucrats) and hence their decisions are unlikely to be challenged by constituency representatives. The results presented here are part of an on going study and should therefore be accepted with great caution.